Sumber Belajar Ekonomi SMA Berbasis Riset Sistem Produksi Gula Batu di CV. Tiga Bintang - Muhammad Nurkholiq Hidayat; Endang Herawan; Rusdiyana Rusdiyana (Jayapangus Press, 2026)
This study aims to describe the sugar cube production system in CV. Three Stars, as well as analyzing its potential as a research-based economic learning resource in high school. This study uses a qualitative approach with a descriptive case study design. Data was collected through observation, in-depth interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the sugar cube production system in CV. Three Stars includes production factors in the form of raw materials, labor, and production equipment. The workforce is 10 people consisting of business owners, machine operators, and packaging personnel. The production process consists of six main stages, including material preparation, cooking, screening, molding/crystallization, colling, and product packaging. The research findings are then transformed into research-based economic learning resources in the form of an E-book entitled